1980
DOI: 10.1038/bjc.1980.250
|View full text |Cite
|
Sign up to set email alerts
|

The use of antisera to epithelial membrane antigen in detecting micrometastases in histological sections

Abstract: We have investigated, by immunocytochemical means, the value of an antiserum raised to milk-fat-globule membranes in detecting metastatic deposits of breast carcinoma in conventional histological sections of liver, lymph nodes and marrow. The antiseum recognizes a membrane component, which we have called Epithelial Membrane Antigen, and which is confined to but widely distributed in epithelial tissues and tumours derived from them. In the sections examined, a greater extent of tumour infiltration was usually f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
1
1

Year Published

1981
1981
2000
2000

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 7 publications
0
49
1
1
Order By: Relevance
“…The results in this paper should be compared with those previously reported by Sloane et al (1980) in which lymph nodes from cases of breast cancer were examined immunohistologically using a polyclonal antiserum directed against epithelial membrane antigen (similar in its specificity to the two monoclonal anti-milk fat globule membrane antigen antibodies used in the present study). However Sloane et al (1980) (Huvos et al, 1971;Attiyeh et al, 1977;Fisher et al, 1978).…”
Section: Discussionmentioning
confidence: 90%
“…The results in this paper should be compared with those previously reported by Sloane et al (1980) in which lymph nodes from cases of breast cancer were examined immunohistologically using a polyclonal antiserum directed against epithelial membrane antigen (similar in its specificity to the two monoclonal anti-milk fat globule membrane antigen antibodies used in the present study). However Sloane et al (1980) (Huvos et al, 1971;Attiyeh et al, 1977;Fisher et al, 1978).…”
Section: Discussionmentioning
confidence: 90%
“…An immunohistochemical stain for EMA can identify minute metastatic deposits of carcinoma in organs such as liver and bone marrow (Sloane et al, 1980;Dearnaley et al, 1981). Our most recent studies have shown that EMA positive cells can be found in the marrows of approximately one third of patients at the time of surgery for a primary breast cancer (Dearnaley et al, 1983).…”
mentioning
confidence: 99%
“…
Epithelial membrane antigen (EMA) (Heyderman et al, 1979) is a membrane component expressed by most epithelial cells, by all breast carcinomas and their metastases but not by the vast majority of normal bone marrow cells (Sloane et al, 1980 (Goding, 1976). Briefly a 1% solution of chromium chloride (CrCl3) in 0.9% sodium chloride (NaCl) was adjusted to pH 5 by the addition of 1 N sodium hydroxide twice-weekly for 3 weeks, then stored without further adjustment in a dark container.
…”
mentioning
confidence: 99%
“…Epithelial membrane antigen (EMA) (Heyderman et al, 1979) is a membrane component expressed by most epithelial cells, by all breast carcinomas and their metastases but not by the vast majority of normal bone marrow cells (Sloane et al, 1980). It has been shown that immunocytochemical staining for EMA can detect very small numbers of breast cancer in bone marrow smears that appear normal by conventional haematological techniques (Dearnaley et al, 1981).…”
mentioning
confidence: 99%